2022
DOI: 10.1088/2515-7620/ac5a69
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen driven niche differentiation in bacterioplankton communities of northeast coastal Bay of Bengal

Abstract: The Bay of Bengal receives nitrogen inputs from multiple sources and the potential role of nitrogen-metabolizing microbial communities in the surface water is not well understood. The nitrogen budget estimate shows a deficit of 4.7 ± 2.4 Tg N yr-1, suggesting a significant role of dissolved organic nitrogen remineralization in fuelling ecosystem processes. Unravelling the process of remineralization leading to increasing concentrations of dissolved inorganic nitrogen (DIN) in coastal ecosystems such as mangrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Relatively higher abundance of the Flavobacteriaceae family in our study sites could indicate the availability of complex macromolecules in these coastal regions. These findings in the BoB confirm previous studies that showed the dominance of Proteobacteria and Bacteroidetes, of which Flavobacteriaceae and Rhodobacteraceae are a part of, in multiple other locations within the bay 13 , 90 .…”
Section: Discussionsupporting
confidence: 90%
“…Relatively higher abundance of the Flavobacteriaceae family in our study sites could indicate the availability of complex macromolecules in these coastal regions. These findings in the BoB confirm previous studies that showed the dominance of Proteobacteria and Bacteroidetes, of which Flavobacteriaceae and Rhodobacteraceae are a part of, in multiple other locations within the bay 13 , 90 .…”
Section: Discussionsupporting
confidence: 90%
“…As a part of the Indian Ocean, the third largest oceanic division of the world 80 , and being surrounded by three different countries, BoB provides ecological habitats and niches for an enormous diversity of microbial groups 13,81 . A recent study conducted by Ghosh et al (2022) revealed that the bacterioplankton community in multiple locations of BoB showed the dominance of Proteobacteria, Bacteroidetes, and Firmicutes as well as the nitrogen-fixing groups such as Nitrospirae, Lentisphaerae, Chloroflexi, and Planctomycetes 82 . Another metagenome-based study of deep-sea sediment samples from 3000m depth of BoB revealed the dominance of Proteobacteria followed by Bacteroidetes, Firmicutes, Cyanobacteria and Actinobacteria 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Such low DO can prolong hypoxia and affect major estuarine ecosystem-level processes, including fluxes and rates linked to carbon and nitrogen biogeochemical cycling. Therefore, maintaining the best possible conditions across the river basins, including coastal and offshore waters, is essential (Karydis and Kitsiou, 2013;Barletta et al, 2019) and crucial for ecosystem functioning and maintaining estuarine biodiversity (Ghosh et al, 2022). Fine sediment deposition is difficult in the regions where strong water currents persist (Mitchell, 2020).…”
Section: Environmental Status Of Mahanadi Estuarymentioning
confidence: 99%
“…In fact, for many estuaries on the east coast of India, premonsoon exhibit the most stressed conditions with excess and continuous accumulation of contaminants (Mitra et al, 2018). However, a good flush-out of pollutants is only possible during the monsoon season (Mulik et al, 2020a), aided further by a breakdown of contaminants owing to changing redox chemistry and consequences on benthicpelagic coupling (Ghosh et al, 2022).…”
Section: Benthic Quality Status Of the Mahanadi Estuarymentioning
confidence: 99%